Construction of tetranuclear metallacycles based on half-sandwich Ir, Rh fragments and pyridyl-substituted ligands with different coordinate vectors. Issue 11 (4th February 2016) - Fan, Qi-Jia; Zhang, Wen-Ying; Lin, Yue-Jian; Jin, Guo-Xin
Abstract : Two-step reactions of [Cp*M(μ-Cl)Cl]2 (M = Ir, Rh), first with AgOTf and then with pyridyl-substituted ligands of different coordinate vectors, resulted in the formation of distorted tetrahedral and parallelogram type tetranuclear metallacycles. Abstract : A series of organometallic macrocycles have been constructed by two-step reactions of [Cp*M(μ-Cl)Cl]2 (M = Ir, Rh), firstly with AgOTf to abstract chloride ions and then with simple pyridyl-substituted ligands—pyridyldipyrromethene (HL 1 ), pyridin-4-yl (1 H -pyrrol-2-yl)methanone (HL 2 ) and pyridine-4-carbohydrazide (HL 3 )—resulting in the formation of the tetranuclear 32-membered metallacycles [(Cp*Ir)(L 1 )]4 (OTf)4 (2a ) and [(Cp*Rh)(L 1 )]4 (OTf)4 (2b ), and the 28-membered metallacycles [(Cp*Ir)(L 2 )]4 (OTf)4 (3a ), [(Cp*Rh)(L 2 )]4 (OTf)4 (3b ), [(Cp*Ir)(L 3 )]4 (OTf)4 (4a ) and [(Cp*Rh)(L 3 )]4 (OTf)4 (4b ). Four target complexes were characterised by single crystal X-ray analyses, revealing that these metallacycles, constructed from half-sandwich metal corners and pyridyl-substituted linkers, form large ring structures. The observed variation in the metallacyclic geometries was explained on the basis of the structural flexibility of the corner fragments, subtle changes in coordination geometries, and changes in the orientation of the coordinate vectors in the given ligands, as well as different dihedral angles between the two binding fragments in the nonplanar ligands.